Tadeusz Reyten Poseł nowogrodzki. - Mielcarzewicz, Teofil (1807-1879) (Poznań i Berlin w Litografii K.A. Simona, 1829)
Przedstawia Tadeusza Rejtana popiersie 3/4 w lewo, głowa na wprost. Ujete od dołu w owal.